2016
DOI: 10.5194/tc-10-1433-2016
|View full text |Cite
|
Sign up to set email alerts
|

Glacier melting and precipitation trends detected by surface area changes in Himalayan ponds

Abstract: Abstract. Climatic time series for high-elevation Himalayan regions are decidedly scarce. Although glacier shrinkage is now sufficiently well described, the changes in precipitation and temperature at these elevations are less clear. This contribution shows that the surface area variations of unconnected glacial ponds, i.e. ponds not directly connected to glacier ice, but that may have a glacier located in their hydrological basin, can be considered as suitable proxies for detecting past changes in the main hy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 64 publications
3
19
0
Order By: Relevance
“…There is also an interhemispheric decline in precipitation over the subtropics (30-40 • N), which is most intense in the Mediterranean and mountainous regions of continental Asia. This shift has been also identified in the GPCP data set (Gu et al, 2016), as well as in various regional studies for the Mediterranean (Hoerling et al, 2012;Philandras et al, 2011), California (Diffenbaugh et al, 2015;Swain et al, 2016), and central Asia (Chen et al, 2011;Salerno et al, 2016). In our results, there are significant shifts in all quantiles of subtropic precipitation over land, except in the United States, where changes are more heterogeneous.…”
Section: Discussionsupporting
confidence: 91%
“…There is also an interhemispheric decline in precipitation over the subtropics (30-40 • N), which is most intense in the Mediterranean and mountainous regions of continental Asia. This shift has been also identified in the GPCP data set (Gu et al, 2016), as well as in various regional studies for the Mediterranean (Hoerling et al, 2012;Philandras et al, 2011), California (Diffenbaugh et al, 2015;Swain et al, 2016), and central Asia (Chen et al, 2011;Salerno et al, 2016). In our results, there are significant shifts in all quantiles of subtropic precipitation over land, except in the United States, where changes are more heterogeneous.…”
Section: Discussionsupporting
confidence: 91%
“…The annual precipitation was found to be decreasing at an alarming rate of −20 mm/year for the last two decades' tenure (Figure ). This decrease of the precipitation amount, particularly in the southern side of Mount Everest (containing large part of this study area), was also seen in the study carried out by Salerno et al (), which inferred to the decreasing trend of precipitation after mid‐1990s to recent years (2013 in their study).…”
Section: Resultssupporting
confidence: 86%
“…This may be because of decline of precipitation in the study area which constitutes the important recharge source for most of the OLs (Basnett et al, 2013). Salerno et al (2016) also observed that the disconnected lake ice ponds decreased significantly over the period due to a reduction in overall precipitation on the southern slopes of Mt Everest in Sagarmatha National Park (SNP). The similar shrinkage of disconnected lakes has also been reported in western Himalaya (Shukla and Qadir, 2016).…”
Section: Temporal Evolution Of Lakesmentioning
confidence: 67%